Maritime logistics and global supply chains: towards a research agenda - Panayides, Photis (My University, 2006)
The derived demand for maritime transport has evolved from a demand for the possession of goods to an integrated demand for the possession of goods that have been added value, timely, reliably and cost-efficiently. This has given rise to the concept of maritime logistics, which represents the theme of the special issue of Maritime Economics and Logistics. This paper discusses the evolution of the maritime logistics concept, reviews the contributions in maritime logistics made by the best papers on the topic presented at the International Association of Maritime Economists (IAME) 2005 Conference and highlights areas for further research
Keywords: Maritime economics; Shipping; Logistics; Business logistics; Transportation